SINTESIS LAPISAN TIPIS (THIN FILM) SnO2 DAN SnO2:Al MENGGUNAKAN TEKNIK SOL-GEL SPIN COATING PADA SUBSTRAT KACA DAN QUARTZ - Yanika Diah Imawanti; Aris Doyan; Erin Ryantin Gunawan (Jurnal Penelitian Pendidikan IPA, 2017)
This study has successfully synthesized SnO2 and SnO2 thin films by doping aluminum (Al) using the technique of sol-gel spin coating on glass and quartz substrates. The basic materials are Tin (II) chloride dihydrate (SnCl2.2H2O) and ethanol (C2H5OH) as solvent.  Material for doping is AlCl3 as much as 0.027 g, 0.053 g and 0.08 g to get Al dopant concentration of 5%, 10% and 15% respectively. The substrate used in this study are glass and quartz with the dimension of 10 mm x 10 mm x 3 mm. Detergent water, distilled water and 70% alcohol were used for the preparation of the substrates. Pure SnO2 sol solution was obtained by dissolving SnCl2.2H2O in ethanol, and SnO2:Al was obtained by adding AlCl3 to the solution of SnO2. The stirring process was done by using a hot plate magnetic stirrer to obtained a homogeneous solution (transparent). Sol solution of pure SnO2 and SnO2:Al were allowed for 24 hours as maturation (aging) process. Solution deposition on a substrate was done with a rotary speed of 2000 rpm for 3 minutes. Heating process was done at the annealing temperature of 200°C to 400°C by using a furnace for 1 hour to grow the crystalline of thin films. This thin films are very appropriate when applied to transparent conductive oxide (TCO) materials with high transparency and conductive character of tin (Sn) and aluminum (Al)Keyword: SnO2‚ aluminum‚ sol-gel, spin coating, substrate